Successful thrombolytic therapy with recombinant tissue plasminogen activator in ischemic stroke after idarucizumab administration for reversal of dabigatran: a case report - Toshiyuki Ohtani; Ryosuke Sintoku; Tasuku Yajima; Naoyuki Kaneko (Journal of Medical Case Reports, 2019)
Abstract Background Idarucizumab is a specific antidote for the anticoagulant dabigatran. Although its efficacy has been recently reported, the drug is still in postmarketing surveillance and requires case data in different emergency settings. A newer intravenous thrombolytic therapy with recombinant tissue plasminogen activator has been proposed after injection of idarucizumab in patients receiving dabigatran; however, the safety and efficacy of this therapy are equivocal because of the limited number of reported cases. We describe a case of a patient with acute lacunar stroke causing dysarthria and hemiparesis successfully treated with intravenous thrombolytic therapy with recombinant tissue plasminogen activator after reversal of dabigatran with idarucizumab. Case presentation A 67-year-old Asian woman was transferred to our emergency center 200 minutes after sudden onset of dysarthria and right-sided hemiparesis. She had been taking dabigatran for prevention of stroke recurrence caused by atrial fibrillation. Diffusion-weighted magnetic resonance imaging revealed a new lacunar infarction near old putamen infarctions. We treated her with intravenous thrombolytic therapy with recombinant tissue plasminogen activator after administering idarucizumab. The time to recombinant tissue plasminogen activator administration was 5 minutes from idarucizumab injection and 269 minutes from symptom onset. The patient’s activated partial thromboplastin times were 68.0 and 43.2 seconds before and after the therapy, respectively. The patient’s neurological symptoms improved significantly after the treatment, and she experienced no adverse events. Conclusions Intravenous thrombolytic therapy with recombinant tissue plasminogen activator after reversal of dabigatran with idarucizumab may be safe and feasible in patients with acute ischemic stroke with lacunar infarct. Furthermore, intravenous thrombolytic therapy with recombinant tissue plasminogen activator could be used in patients in emergency settings until just before the end of the recommended time limit within which it needs to be administered because of the immediate effect of idarucizumab.